Pengaruh Pendekatan Matematika Realistik Terhadap Kemampuan Penalaran Matematis Dalam Pembelajaran Matematika - Simorangkir, Imelda (Unika Santo Thomas Medan, 2019)
The purpose of this study was to look at the effect of realistic mathematics learning on students 'reasoning abilities and to determine students' responses to mathematics learning with realistic mathematical approaches and their relation to mathematical reasoning abilities. This research was conducted at YPAK Galang of Junior High School at 2017/2018 Academic Year. The method used in this study is a quasi-experimental method with the design of Non Equivalent Control Group Design. The sample in this study was 64 students consisting of 32 students for the experimental group and 32 students for the control group. The data analysis technique used in this study is a regression test. Based on the calculation of hypothesis regression linearity test (i) Ha is accepted and Ho is rejected because F_count < F table is -44.40 < 1.88 then the regression form is linear, and for testing the significance of hypothesis regression (ii) Ha is accepted and Ho is rejected because of Fcount > Ftable that is 44.402 > 3.96 means that there is a relationship of variable (X) to varabel (Y). Data collection techniques in the form of a questionnaire consisting of 14 items statement. Based on the calculation of questionnaire data on students 'responses to realistic mathematical learning, the percentage of students' responses that stated yes was 75.38% and the percentage of responses that stated was not 24.62%. This shows that the student response questionnaire is positive.